Removal of antibiotics in aqueous media by using new synthesized bio-based poly(ethylene terephthalate)-TiO2 photocatalysts. (November 2019) - Malesic-Eleftheriadou, Neda; Evgenidou, Eleni Ν.; Kyzas, George Z.; Bikiaris, Dimitrios N.; Lambropoulou, Dimitra A.
Abstract: Recently the synthesis and application of bio-based composite materials, which contain polymeric and inorganic units such as TiO2, has gained much attention in the field of water/wastewater treatment, due to their better (and more practical) performance parameters. In the present study, recycled poly(ethylene terephthalate) (PET) has been used and evaluated as supporting polymer for Aeroxide P25 TiO2 immobilization. PET-TiO2 composite films were synthesized at different TiO2 content (10%, 30% and 47% TiO2 ) and characterized with different techniques such as X-ray Powder Diffraction (XRD), Thermogravimetric analysis (TGA), Differential scanning calorimetry (DSC), Scanning electron microscopy (SEM), etc. The photocatalytic activity of the new (synthesized) bio-based TiO2 composite films was investigated under simulated solar irradiation for the degradation of a mixture of antibiotic pharmaceuticals (Isoniazid, Metronizadole, Sulfadiazine, Sulfamethoxazole, Trimethoprim, Norfloxacin, Moxifloxacin and Lincomycin). The immobilization of TiO2 was successful in all cases and by increasing the photocatalyst concentration results in higher photocatalytic efficiencies. The new composite films were tested two times to assess their reusability, which found to be better for PET-10%-TiO2 composite films; therefore the latter has been used for further investigation thus exhibiting good stability even after five cycles. The results showed that PET-10%-TiO2 was efficient in degrading the antibiotic mixture in water and in wastewater matrix. Highlights: The photocatalytic activity of novel biobased-PET-TiO2 composite films was tested. XRD, TGA, DSC, SEM characterizations were performed. At higher TiO2 loading, reusability of the photocatalysts decreased. PET-10% wt TiO2 exhibited high performance even after 5 cycles. Antibiotics degradation was achieved in water and wastewater matrix.